New method of assessing visual acuity with pictures. Issue 2 (February 1983) - Kay, H
Abstract : It is never easy to assess accurately the vision of an illiterate child. Children under the age of 3 who are unable to understand and co-operate with tests using shapes and a key card present an even greater problem. All available subjective tests for this age group may maintain a small child's interest, but the accuracy of the recorded vision is very much in doubt. The new test described below is designed for 2-3-year old children. It combines the well recognised advantages of using pictures to gain the child's attention with the accuracy of a graded test based on Snellen's chart sizing. It is therefore both a practical and more accurate alternative test for this age group.